Senescence: A DNA damage response and its role in aging and Neurodegenerative Diseases - Shreeya, Tejal; Ansari, Mohd Saifullah; Kumar, Prabhat; Saifi, Muskan; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag Eldin I. (Frontiers in Aging, 2024)
Senescence is a complicated, multi-factorial, irreversible cell cycle halt that has a tumorsuppressing effect in addition to being a significant factor in aging and neurological diseases.Damaged DNA, neuroinflammation, oxidative stress and disrupted proteostasis are a few of the factors that cause senescence. Senescence is triggered by DNA damage which initiates DNA damage response. The DNA damage response, which includes the formation of DNA damage foci containing activated H2AX, which is a key factor in cellular senescence, is provoked by a double strand DNA break. Oxidative stress impairs cognition, inhibits neurogenesis, and has an accelerated aging effect. Senescent cells generate pro-inflammatory secretory phenotypes known as senescence-associated secretory phenotypes (SASP). These pro-inflammatory cytokines have an impact on neuroinflammation, neuronal death, and cell proliferation. While it is tempting to think of neurodegenerative diseases as manifestations of accelerated aging and senescence, this review will present information on brain ageing and neurodegeneration as a result of senescence and DNA damage response.